Efficacy of Off-Label Therapy for Non-alcoholic Fatty Liver Disease in Improving Non-invasive and Invasive Biomarkers: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Luo, Qian; Wei, Ruojun; Cai, Yuzi; Zhao, Qihan; Liu, Yuning; Liu, Wei Jing (Frontiers in Medicine, 2022)
The aim of this network meta-analysis to evaluate the effects of vitamin E, pioglitazone, sodium-glucose cotransporter-2 (SGLT- 2)inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists in NAFLD patients with or without Diabetes Mellitus.RCTs that compared the effects of 4 different drugs of NAFLD patients with or without Diabetes Mellitus.27 trials including 3416 patients proved eligible.results refer to vitamin E, pioglitazone,GLP-1 receptor agonists,SGLT2 inhibitors.Firstly, A placebo was used as a reference.δ-tocotrienol was obviously superior to placebo in decreasing GGT level.Semaglutide,Ipragliflflozin and Pioglitazone were obviously superior to placebo in decreasing ALT level.Semaglutide,Pioglitazone and Dapagliflozin were obviously superior to placebo in decreasing AST level.Tofogliflozin and Pioglitazone were obviously superior to placebo in decreasing K-18 level.Liraglutide was obviously superior to placebo in decreasing CAP level.Liraglutide,Pioglitazone and vitaminE were obviously superior to placebo in increasing in resolution of NASH.As for pairwise comparisons, Semaglutide and Pioglitazone were obviously superior to Liraglutide in decreasing ALT level,Semaglutide was obviously superior to Dulaglutide in decreasing ALT level,Semaglutide was obviously superior to Empagliflozin,Liraglutide,Dulaglutide and Tofogliflozin in decreasing AST level,Pioglitazone was obviously superior to Ipragliflozin in decreasing GGT level,δ-tocotrienol was obviously superior to Liraglutide in decreasing GGT level,Tofogliflozin and Pioglitazone were obviously superior to dulaglutide in decreasing K-18 level,Pioglitazone was obviously superior to vitaminE in increasing resolution of NASH.Thirdly,Liraglutide treatment had the highest SUCRA ranking in decreasing the CAP,ELF,and increasing resolution of NASH.Pioglitazone treatment had the highest SUCRA ranking in decreasing the LFC and Fibrosis score.Tofogliflozin treatment had the highest SUCRA ranking in decreasing the K-18,Dapagliflozin treatment had the highest SUCRA ranking in decreasing the GGT level.Semaglutide,treatment had the highest SUCRA ranking in decreasing the ALT and AST.The network meta-analysis provides evidence-based evidence for the efficacy of vitamin E, pioglitazone, SGLT-2 inhibitor and GLP-1 receptor agonist in NAFLD patients with or without diabetes. In order to find the best guide-level drugs, it is necessary to further include RCT experiments in these off-label drugs, so that patients and clinicians can make wise decisions together.